Phytochemical and antibacterial analyses of essential oils extracted from the leaves of Euodia suaveolens scheff - Sidharta, Boy Rahardjo; Atmodjo, Patricius Kianto (Pharmaciana, 2024)
Euodia suaveolens is one of the plants that ancient people in Indonesia used due to its manifold benefits. Earlier research on this plant was mostly done on its potency as a mosquito repellent. This present study aims to determine the phytochemical and antibacterial analyses of the essential oils (EOs) extracted from the leaves of E. suaveolens. The EOs of the leaves of E. suaveolens were extracted by steam distillation method and were analyzed phytochemically utilizing the GC-MS technique to determine the chemical constituents. The chemical components were tested on four pathogenic bacteria Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis utilizing the diffusion agar method. The results showed that the main compounds extracted from the EOs were delta curcumene, evodone, globulol, limonene, linalool, longipinenepoxide, menthofuran, and p-mentha-1,8-diene. The antibacterial analysis of these compounds showed potential activities to inhibit the growth of four pathogenic bacteria tested, but the inhibition zones formed were still lower compared to commercial antibiotic kanamycin. E. suaveolens EOs exhibited diameter of zone of inhibition as follows 2.03 plus minus 0.22, 0.50 plus minus 0.49, 1.38 plus minus 0.10, 1.40 plus minus 0.27 cm to E. coli, P. aeruginosa, S. aureus, and S. epidermidis while kanamycin showed 3.43 plus minus 0.08, 3.25 plus minus 0.08, 3.38 plus minus 0.12, and 3.18 plus minus 0.24 cm respectively. These results recommend that the main compounds extracted from the EOs of the leaves of E. suaveolens be explored further to determine their potencies as new antibiotic medications.